The importance of early intervention programs on the development of special needs individual - Abdullah, Borhannudin; Wan Omar, Wan Nomi (Human Resource Management Academic Research Society, 2018)
The purpose of this study is to improve special needs children with problem in motor skills through intervention programs. Special needs children who have motor issues will have developmental delay problem. The study took a closer look into these special needs children with developmental delay problem. These children were carefully observed and monitored to record their responses and progresses throughout the intervention processes. These children would go through a screening test using Denver II instrument to identify the baseline of their developmental domain potential and issues before they started the intervention programs. The observation lasted for 3 months. The progresses of the students were charted in the form of bar chart. The result shows that the intervention programs have improved the performance of the children and their overall developmental domain. There are significant differences between before and after the intervention. Thus, the interventions are able to increase the children gross motor skills. The study also identifies the support and involvement of the parents as important factor in ensuring the early intervention to be implemented successfully.